Semi-Structured Interview The List of Basic Developmental Information for Children and Adolescents (LBDI-CA) - Krstić, Miroslav Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Many psychodiagnosticians consider the interview to be the basic and irreplaceable method and even the “crown witness” of the psychodiagnostic battery. Accepting that point of view and acknowledging the fact that semi-structured interviews have been gaining in popularity, this paper aims to offer psychologists (undergraduate and graduate psychology students, psychology interns, those specializing in and specialists of medical psychology) a solid semi-structured interview. Based on theoretical knowledge and grounded in decades of practical experience, including thousands of interviews conducted with children, adolescents and their parents, this paper presents a semi-structured interview called The List of Basic Developmental Information for Children and Adolescents (LBDI-CA). We hope that our co-practitioners will find this semi-structured interview useful as a foremost technique from the developmental age psychodiagnostic battery for the assessment of children and adolescents.